Bridgeless Buck-Boost PFC Converter with Three-State Switching Cell - Morais, Douglas Carvalho [UNESP]; Jose Mendes De Seixas, Falcondes [UNESP]; Oro Arenas, Luis De [UNESP]; Carvalho Souza, Lucas [UNESP]; Souza Da Costa E Silva, Luciano De (Institute of Electrical and Electronics Engineers (IEEE), 2019)
In this paper, a bridgeless buck-boost converter with power factor correction is proposed, using a three-state switching cell named of B configuration, operating in continuous conduction mode. The bridgeless technique allows the bridge rectifier inclusion switched on power grid frequency, in the high frequency DC-DC converter stage, reducing the stages number required and increasing the structure reliability. Due to three-state switching cell configuration, there is a current stress division by half of the inductor current in all of circuit semiconductors. Moreover, the ripple frequency on converter energy storage elements is twice switching frequency value, which make easier the design of input and output passive filters and reduces the converter's volume and weight. Preliminary simulation results prove the converter effectiveness on power factor correction, keeping output voltage stable in a specified operation point, with a total harmonic distortion of the input current less than 2%.
Keywords: bridgeless buck-boost converter; continuous conduction mode; power factor correction; three-state switching cell; total harmonic distortion